Chiral phosphine-mediated intramolecular [3 + 2] annulation: enhanced enantioselectivity by achiral Brønsted acid. Issue 7 (1st June 2017) - Yao, Weijun; Yu, Zhaoyuan; Wen, Shan; Ni, Huanzhen; Ullah, Nisar; Lan, Yu; Lu, Yixin
Abstract : Enantioselective intramolecular [3 + 2] annulation of chalcone–allenes catalyzed by amino acid-derived phosphines and achiral Brønsted acids has been developed. Abstract : Enantioselective intramolecular [3 + 2] annulation of chalcones bearing an allene moiety has been successfully developed. The reaction was effectively promoted by amino acid-derived phosphines, in combination with achiral Brønsted acids. Dihydrocoumarin architectures were constructed in high yields and with excellent enantiomeric excesses. Theoretical studies via DFT calculations revealed that the hydrogen bonding network induced by achiral Brønsted acids/chiral phosphines could more efficiently distinguish between two enantioselective pathways, thus leading to enhanced enantioselectivity.